Presentation of the Dean - Rojas Tuya, Santiago (2024)
It is an honor to address you in this special edition of our magazine, dedicated to promoting research and innovation in the field of engineering. On this occasion, I would like to emphasize that we are dedicated at the Faculty to continue raising the quality and continuing education that benefits not only our students, but also our colleagues and friends in the profession.